New Mortar Mixes with Chemically Depolymerized Waste PET Aggregates. (12th December 2020) - Foti, Dora; Lerna, Michela
Abstract : Nanoparticles are used in innovative mortars in order to improve their engineering properties. In this paper, recycled PET (polyethylene terephthalate) nanoparticles were used as a substitute for sand in mortars. PET aggregates were obtained cutting water bottles wastes into many small sized pieces and the plastic fibres were treated through chemical depolymerization process. Mortars with different percentages of PET were tested to determine their physical and mechanical (flexural and compressive strength) properties. Specific attention is given to the heat-transfer capacity of the cement pastes investigated. The results of the mechanical tests showed a reduction of the flexural and compressive strength values when the amount of PET nanoparticles increase. The thermal conductivity tests showed that chemically depolymerized PET nanoparticles derived from plastic wastes reduced the heat conduction capacity of the mortar. Therefore, the innovative mortars here tested can be considered for thermal insulation applications in the construction field with the advantage of recycling waste PET.